Continuous follicle-stimulating hormone exposure from pituitary adenoma causes periodic follicle recruitment and atresia, which mimics ovarian hyperstimulation syndrome - Morishita M; Shimizu A; Ikeda K; Kitajima Y; Baba T; Kanaya M; Honnma H; Endo T; Saito T (Dove Medical Press, 2012)
Mika Kanaya,1 Tsuyoshi Baba,2 Yoshimitsu Kitajima,2 Keiko Ikeda,2 Ayumi Shimizu,2 Miyuki Morishita,2 Hiroyuki Honnma,3 Toshiaki Endo,2 Tsuyoshi Saito21Mika Ladies Clinic, 2Department of Obstetrics and Gynecology, Sapporo Medical University, School of Medicine, 3Kamiya Ladies Clinic, Sapporo, JapanContext: Follicle-stimulating hormone (FSH)-secreting pituitary adenoma is usually a nonfunctioning tumor, but in rare cases it may develop into ovarian hyperstimulation. Several reports have revealed that serum FSH levels are normal to slightly high in patients with combined FSH-secreting pituitary adenoma with ovarian hyperstimulation. This finding is different from iatrogenic ovarian hyperstimulation syndrome (OHSS), which is associated with extremely high levels of FSH.Objective: To describe the clinical course of two patients who developed OHSS from FSH-secreting pituitary adenoma.Results: Endocrine studies of the two cases revealed that FSH levels were normal or slightly increased, but luteinizing hormone levels were low to undetectable. Their estradiol (E2) levels were intriguing: levels fluctuated drastically over 6 weeks in Case 1, but stayed flat in Case 2. Ultrasonographic examinations showed bilaterally enlarged multicystic ovaries, and magnetic resonance imaging indicated pituitary tumors. Transsephenoidal resection of the tumors ameliorated the symptoms and pathological diagnosis revealed FSH-secreting pituitary adenomas.Conclusion: As is not the case in iatrogenic OHSS, even a small to moderate amount of FSH stimulation, which is continuously secreted by a pituitary adenoma, can cause ovarian hyperstimulation. Although FSH-secreting pituitary adenoma can cause ovarian hyperstimulation, an extremely high amount of E2 biosynthesis from granulosa cells seldom occurs.Keywords: pituitary adenoma, OHSS, FSH, estradiol, luteinizing hormone